Evaluation of Kinetic Parameters of α-Amylase in the Presence of the Flavonoid Rich-Extract of Ficus carica L., an In-vitro Study: Kinetic Parameters of α-Amylase in the Presence of Fig Flavonoids - Mohadjerani, Maryam; Sanaei, Zeynab (Iranian Journal of Pharmaceutical Sciences, 2022)
Plants contain different chemical constituents with the potential for insulin-mimetic action. Reduction of insulin resistance and inhibition of α-amylase have been used as therapeutic strategies in treating diabetes. Considering the possible role of normal flora bacteria in the human body’s metabolism, the bacterial enzyme α-amylase may also be of interest from this point of view. This study investigated the effect of flavonoid-rich extracts of the fig plant (Ficus carica L.) on bacterial α-amylase. The flavonoid-rich extracts were obtained from fig leaves and fruits by solvent extraction. Subsequently, the kinetic parameters of the α-amylase enzyme in the presence of these extracts were studied using the Bernfeld method. The evaluated IC50 values for acarbose, leaf and fruit extracts, and quercetin were equal to 0.112, 2.029, 0.195, and 0.071 mg/mL, respectively. The separately determined kinetic parameters Km and Vmax of the α-amylase in the presence of the fruit extract were 551.488 mM and 0.018 mM/min, and in the presence of the leaf extract, were 991.518 mM and 0.016 mM/min, respectively. The mode of inhibition was determined to be competitive by both extracts. According to our investigations, fig plant flavonoid-rich extract can be suggested as a suitable alternative to chemical compounds for therapeutic use in diabetes mellitus.